1986
DOI: 10.1111/j.1752-0606.1986.tb00638.x
|View full text |Cite
|
Sign up to set email alerts
|

Marriage Encounter Weekends: Couples Who Win and Couples Who Lose

Abstract: This study examined interview and essay data for 50 married couples who had the most positive or most negative reactions in a larger sample of participants in Marriage Encounter weekends. We were interested in describing the experiences of couples who years later believed they were strongly helped by the program or who believed their marriages deteriorated because of the program. Content analysis of interview transcripts and written essays indicated that 7 couples experienced highly positive changes apparently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

1988
1988
2002
2002

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 8 publications
1
22
0
1
Order By: Relevance
“…This seems to support the findings of Doherty et al (1986) that preventive interventions can have both positive and negative effects. Analyses of group means simply focus on whether average differences between groups exist; Jacobson's procedure can provide data about the direction and intensity of change within a group.…”
Section: 8%) In the Control Groupsupporting
confidence: 89%
“…This seems to support the findings of Doherty et al (1986) that preventive interventions can have both positive and negative effects. Analyses of group means simply focus on whether average differences between groups exist; Jacobson's procedure can provide data about the direction and intensity of change within a group.…”
Section: 8%) In the Control Groupsupporting
confidence: 89%
“…For example, Smith and his associates' (1980) metaanalysis of psychotherapy effectiveness found that about 9% of the effect-size measures were negative. Doherty, Lester, and Leigh (1986) reported that of the couples who were strongly affected by a "marital encounter" weekend, 50% were helped and 5096 were negatively affectecLIntheirrearralySisof datafromtheNIMHCollaborativeDepression Study, Ogles, Lambert, and Sawyer (1995) found that 13% of clients who received cognitive behavioral therapy were judged to have a "reliable negative" treatment outcome.…”
Section: Sumq Datamentioning
confidence: 98%
“…Gurman and Kniskern (1977) raise questions about the long-term effectiveness of enrichment programs, suggesting that change may be illusory. Doherty and colleagues (Doherty & Walker, 1982;Doherty et al, 1986;Lester & Doherty, 1983), in a series of studies evaluating Marriage Encounter, raise concerns over deterioration effects, which are generally not measured in research on marriage enrichment.…”
Section: Dale R Hawley and Davzd H Olsonmentioning
confidence: 95%